E-225 Mechanical thrombectomy for the treatment of basilar artery occlusion: factors associated with the delayed door to puncture time. (23rd July 2022) - Nguyen, B; Yuki, I; Stradling, D; Xu, J; Golshani, K; Yu, W; Suzuki, S
Abstract : Background: Performing mechanical thrombectomy (MT) in patients with basilar artery occlusion (BAO) is currently not evidence-based. It is also often encountered in the real-world practice that the delayed initiation of the MT happens for this patient groups due to relatively unclear focal neurological signs and other medical confounding factors. Methods: We retrospectively analyzed the angiographical and clinical outcomes of consecutive BAO patient who underwent MT at a single center. Also, the Onset to treatment (OTT), Door to Puncture (DTP) time were compared with those in anterior circulation large vessel occlusion (ACLVO) group who underwent MT in the same time period. The factors associated with the delayed initiation of the MT were analyzed. Results: A total of 271 patients underwent mechanical thrombectomy at UCI Medical Center between Jan 2016 and June 2021. Of these, 32 patients diagnosed as BAO by CTA and underwent MT were included in the study. Successful reperfusion was achieved in 28 cases (87.5%), and symptomatic ICH occurred in 3 cases (9.4%). Nine patients (28.1%) showed good clinical outcomes (mRS 0–3) at 3 months. The median Onset to Puncture Time (OTT) was 340 min. The median DTP time (145 min) was significantly longer as compared to the ACLVO patients (99 min) (p value = 0.04). Of the 6 patients who showed significant delay in the initiation of intervention (DTP>300 min), 5 patients (83.3%) did not have the initial 'stroke-code activation' at the time of ED arrival. The cause of the delay was due to lack of cortical sign (3), bilateral spontaneous sustained clonus, which misinterpreted as seizure (1), AMS with non-focal neurological signs interpreted as encephalopathy (2). Conclusion: DTP of the patients who underwent MT for BAO was significantly longer than patients with ACLAO. The delayed activation of stroke code was associated with lack of cortical sings which are markers of ACLVO. Establishment of BAO screening in the ED assessment and prompt activation of Stroke code may contribute to the improvement of MT treatment for the BAO patients. Disclosures: B. Nguyen: None. I. Yuki: None. D. Stradling: None. J. Xu: None. K. Golshani: None. W. Yu: None. S. Suzuki: None.